Pre-operative conditioning of patients having pulmonary tuberculomes with local catarrhal endobronchitis - A. A. Strelis; A. K. Strelis; Ye. V. Nekrasov (Бюллетень сибирской медицины)
A new method of preoperative conditioning of patients having pulmonary tuberculomes with catarrhal endobronchitis. The base of the method is electrical vibrational accupressure which has several influence on breathing organs. It is confirmed by the dynamics of clinical, hematologic, endoscopic, functional scintigraphic biochemical data before and after the treatment. Aimed at treating local catarrhal endobronchites, parameters ( frequency from 35 to 40 Hz, amplitude from 0.6 to 0.7 mm) are used which coincide with functional rhythm of bronchial tree and cilia of fibrillar epithelium of its mucous membranes.